Impact of Digital Marketing on Purchasing Decisions for Electronic Goods: An Analytical Study of Urban Indian Consumers. (Journal of Informatics Education and Research, 2025)
Digital marketing has emerged as a game-changer in modern business, reshaping how organizations connect with consumers and influence their purchasing decisions. In the dynamic and rapidly growing Indian digital marketplace, electronic goods represent a critical segment where digital marketing's potential can be most effectively leveraged. This study explores the impact of six key digital marketing dimensions—Search Engine Promotion, Content Promotion, Online Public Relations, Social Media Marketing, Affiliate Marketing, and Email Marketing—on consumer purchasing behaviour in urban India.